2021
DOI: 10.3390/heritage4040228
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Virtual Humans for Cultural Heritage Applications

Abstract: Virtual Humans are becoming a commodity in computing technology and lately have been utilized in the context of interactive presentations in Virtual Cultural Heritage environments and exhibitions. To this end, this research work underlines the importance of aligning and fine-tuning Virtual Humans’ appearance to their roles and highlights the importance of affective components. Building realistic Virtual Humans was traditionally a great challenge requiring a professional motion capturing studio and heavy resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…They can be virtual humans or real-life actors. How to create quality virtual humans and their contribution to immersion are explained in [21]. On the other hand, real actors give a different level of immersion and add life to VR narration [22].…”
Section: Vr In Cultural Heritagementioning
confidence: 99%
“…They can be virtual humans or real-life actors. How to create quality virtual humans and their contribution to immersion are explained in [21]. On the other hand, real actors give a different level of immersion and add life to VR narration [22].…”
Section: Vr In Cultural Heritagementioning
confidence: 99%
“…The ARCO system [18,19] provides customized tools for Virtual Museum (VM) environments, ranging from the digitization of museum collections to the tangible visualization of both museum galleries and artworks. In [20], Virtual Humans (VHs) are used in an AR setting to present narratives on the everyday life of workers in a mastic factory narrated by the workers themselves appearing virtually within the exhibition.…”
Section: Interactive Technologies For Chmentioning
confidence: 99%
“…Research has shown that VHs can affect the virtual experience and stimulate attention and involvement [56][57][58]. Furthermore, their contribution to achieving the suspension of disbelief has been recognized [59]. Narratives, when successfully used for guiding the user through a Virtual Museum, motivate visitors to stay longer and see more [60].…”
Section: Virtual Humansmentioning
confidence: 99%
“…VHs can bring these experiences to a wider audience, including people with disabilities [61], as well as provide a welcome invitation for discovery [62,63]. As such, several approaches have been presented for the implementation of realistic VHs, including segmentation of the motion files acquired through the recording of craft practitioners and narrators (e.g., [59,61,62]).…”
Section: Virtual Humansmentioning
confidence: 99%